2013 IEEE 21st International Symposium on Modelling, Analysis and Simulation of Computer and Telecommunication Systems 2013
DOI: 10.1109/mascots.2013.50
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Popularity Characterization and Modeling of User-Generated Videos

Abstract: Abstract-This paper presents new results on characterization and modeling of user-generated video popularity evolution, based on a recent complementary data collection for videos that were previously the subject of an eight month data collection campaign during 2008/09. In particular, during 2011, we collected two contiguous months of weekly view counts for videos in two separate 2008/09 datasets, namely the "recently-uploaded" and the "keyword-search" datasets. These datasets contain statistics for videos tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Although this second data collection took place well after the longitudinal collection was terminated, the crawls still provided information about 1,456,230 (60.86%) of the observed videos. Similar numbers have been observed by Islam et al [23], who were able to observe 67.13% and 55.23% of random (recently uploaded) and popular (keyword search) videos, respectively, when revisiting the YouTube site looking for videos from a prior data collection that had been carried out more than two years earlier [6]. Figure 1 shows the weekly viewing pattern over the duration of our longitudinal data collection period.…”
Section: Methodssupporting
confidence: 85%
“…Although this second data collection took place well after the longitudinal collection was terminated, the crawls still provided information about 1,456,230 (60.86%) of the observed videos. Similar numbers have been observed by Islam et al [23], who were able to observe 67.13% and 55.23% of random (recently uploaded) and popular (keyword search) videos, respectively, when revisiting the YouTube site looking for videos from a prior data collection that had been carried out more than two years earlier [6]. Figure 1 shows the weekly viewing pattern over the duration of our longitudinal data collection period.…”
Section: Methodssupporting
confidence: 85%
“…Focusing on YouTube videos, Borghol et al [2011] showed how weekly based views can be used to model video popularity, and designed a model to determine the number of videos that may exceed some popularity thresholds. This work was recently revisited by Islam et al [2013], who showed that the weekly based modeling of popularity is still valid even years after video upload, but the synthetic model proposed for predicting the distribution of popularity of a group of videos is not. Zhou et al [2011] showed the importance of links to related videos to video popularity.…”
Section: Popularity Evolution Of Ugcmentioning
confidence: 99%
“…It is noteworthy that other minor restrictions, not described here, were included in the query criteria in order to exclude irrelevant registers from the search results, such as conference presentations, journal editorials, and duplicated results. Additionally, it is important to mention that research papers similar to those of Birke et al 2013, Islam et al (2013) and Benmoussa et al (2013) were not part of this survey, although they regard systems' characterisations. This is due to the absence of the term 'workload characterisation' in their titles, keywords and abstracts.…”
Section: Data Collectionmentioning
confidence: 99%